Antisense ribosomes: rRNA as a vehicle for antisense RNAs. - Sweeney, R (1996)
Although rRNA has a conserved core structure, its size varies by more than 2000 bases between eubacteria and vertebrates, mostly due to the size variation of discrete variable regions. Previous studies have shown that insertion of foreign sequences into some of these variable regions has little effect on rRNA function. These properties make rRNA a potentially very advantageous vehicle to carry other RNA moieties with biological activity, such as "antisense RNAs." We have explored this possibility by inserting antisense RNAs targeted against one essential and two nonessential genes into a site within a variable region in the Tetrahymena thermophila large subunit rRNA gene. Expression of each of the three genes tested can be drastically reduced or eliminated in transformed T. thermophila lines containing these altered rRNAs. In addition, we found that only antisense rRNAs containing RNA sequences complementary to the 5' untranslated region of the targeted mRNA were effective. Lines containing antisense rRNAs targeted against either of the nonessential genes grow well, indicating that the altered rRNAs fulfill their functions within the ribosome. Since functional rRNA is extremely abundant and stable and comes into direct contact with translated mRNAs, it may prove to be an unparalleled vehicle for enhancing the activity of functional RNAs that act on mRNAs.